Strategic Financial Decision dalam Ketidakpastian Bisnis: Studi Kasus PT Japfa Comfeed Indonesia Tbk - Regina (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to analyze strategic financial decision-making under conditions of business uncertainty at PT Japfa Comfeed Indonesia Tbk. Economic instability, fluctuating raw material prices, and changes in market demand are the main challenges facing the agribusiness company. The research method used is a quantitative descriptive approach using secondary data in the form of the 2024 financial report. Analytical techniques include financial ratio analysis, risk identification, and evaluation of turnaround strategies. The results indicate that the company has relatively stable financial performance with a Current Ratio of 1.8, a DER of 1.1, and an ROE of 19.4%, reflecting its ability to generate strong profits. However, the company still faces production cost pressures and dependence on raw materials. Recommended strategies include production cost efficiency, product diversification, and operational digitalization. Furthermore, investment decisions in modern technology are considered capable of increasing the company's efficiency and competitiveness. The implications of this study indicate that strategic financial decision-making is crucial for maintaining business sustainability amidst economic uncertainty.